The Role of the Village Head in Implementation of TMMD in Group 8 Jambenenggang Village - Yepi Sopian; Yulia Saputri; Ulfah Dulyanti; Salamatu Sa’diyah; Siti Nurasiah Jamil; Ririn Kurniati (Indonesian Journal of Society Development, 2023)
Participation of village leaders and community leaders in the TMMD (TNI Manunggal Bangun Desa) program in Jambenenggang Village, Kebonpedes District. One of the success principles of the program is road repair and bridge construction. This is a development approach model that combines the role and participation of the village head and the community in general. Society is not only an object but also the subject of development. In this case, the government is only a mover and facilitator, while the community becomes an actor in development activities carried out jointly, where development planning is guided more by the participation of the village head and the community, namely. H. Development plans or programs are made in accordance with the needs of the community. The research method used is qualitative. Data collection techniques using methods, observation and documentation. Based on the results of the research, the participation of the village head and the community in decision making is quite good because they are involved in village development activities by the TNI Group. The implementation stage of community development is only related to work assignments. At the evaluation and monitoring stage from the village head and the community, the implementation of the TMMD program activities was also monitored and there was no criticism of the TMMD program either from the community